2015
DOI: 10.1136/thoraxjnl-2014-205982
|View full text |Cite
|
Sign up to set email alerts
|

Scoring criteria for portable monitor recordings: a comparison of four hypopnoea definitions in a population-based cohort

Abstract: Interpretation of PM recordings using hypopnoea criteria which include 3% desaturation without PWA drops as EEG arousal surrogate showed the best diagnosis accuracy compared with full PSG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 36 publications
0
34
1
Order By: Relevance
“…Type 3 monitors lack EEG signals for determination of sleep times that may lead to inaccurate AHI estimations. However, a recent study comparing type 3 portable monitor device with PSG in a general population sample found that portable monitor AHI had good concordance with PSG AHI …”
Section: Discussionmentioning
confidence: 95%
“…Type 3 monitors lack EEG signals for determination of sleep times that may lead to inaccurate AHI estimations. However, a recent study comparing type 3 portable monitor device with PSG in a general population sample found that portable monitor AHI had good concordance with PSG AHI …”
Section: Discussionmentioning
confidence: 95%
“…In fact, rescoring with only portable monitor parameters using a 3% desaturation criteria, which was similar to what we used for our primary analysis, had the best diagnostic accuracy. 26 In conclusion, we found that the Berlin questionnaire may be used as a screening tool in the general population in view of its good sensitivity and high negative predictive value in ruling out severe OSA.…”
Section: -23mentioning
confidence: 99%
“…irdly, we diagnosed SDB based on type III portable monitor rather than inlaboratory polysomnography, the gold standard method for SDB diagnosis. A previous population-based study showed a good AHI concordance between portable monitors and polysomnography, but portable monitors tended to slightly underestimate AHI [22]. However, in the present study, portable monitoring was conducted in hospital by trained clinicians, instead of at home by the patients themselves, to ensure the accuracy of the testing and reducing the discordance.…”
Section: Discussionmentioning
confidence: 79%